Penggunaan layanan open library dalam memenuhi kebutuhan informasi mahasiswa Telkom University - Oktaviani, Fikri Dwi; Yusup, Pawit M; Khadijah, Ute Lies Siti (Universitas Padjadjaran, 2017)
This study aimed to find out the use of open library digital library services in meeting the information needs of Telkom University students. The study used the qualitative method with case study approach. Data collection techniques were conducted through interviews with Telkom University students, observation, and literature study. Study results showed that the initial stage was based on the motivation and goals arising from self-awareness and the need to increase knowledge in completing tasks and scientific works (thesis/TA). Browsing began with authentication using an SSO account (Igracias), and information retrieval began with using a simple search facility. Students also used the internet to access various other sources with the Google search engine to further enrich the required information. Then, At the formulation stage, students conducted brainstorming by learning and understanding the problem-solving process related to the appropriate topic and discussing it with friends, lecturers, or people who were considered understandable and could be invited to discuss related topics that were being deepened. The collection stage was done by downloading the file and storing it in their laptop folder. At the presentation stage, students would feel satisfied after getting the information so it is possible to do monitoring. The presentation was performed in the form of writing a new document or as a complement in both the completion of lecture assignments (proposal and paper) as well as the writing of scientific papers (thesis/TA).